Kewenangan Menteri Dalam Negeri dan Pemerintah Daerah dalam Menetapkan Faktor Penyesuai Sewa Barang Milik Daerah Berkaitan dengan Berlakunya Peraturan Menteri Dalam Negeri Nomor 7 Tahun 2024 - Yuyun Istianah; Rusdianto Sesung (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the authority of the Minister of Home Affairs and Regional Governments in determining the rental adjustment factor and its implications for the management of Regional Government Property. The study is motivated by the enactment of Regulation of the Minister of Home Affairs Number 7 of 2024, which regulates the rental adjustment factor for the placement of telecommunications infrastructure and relates to the need for Regional Governments to optimize regional revenue from asset utilization amid changing economic conditions and property values, while still considering the principles of public service and fairness. This research employs a normative juri dical method with statutory and conceptual approaches. Primary data were obtained through interviews with relevant stakeholders, while secondary data were derived from legislation, policy documents, and legal literature concerning regional asset management. The findings indicate that Regional Governments have the authority to manage Regional Government Property, including determining the rental adjustment factor, based on Law on Regional Government (Indonesia) and other regulations concerning the management of regional assets. Such authority must be implemented in a transparent and accountable manner by considering the economic value of assets and the public interest. Effective tariff adjustments can significantly contribute to increasing Regional Original Revenue and support urban development financing; however, the determination of the rental adjustment factor by the Minister of Home Affairs creates implications for the implementation of regional asset management by Regional Governments. Therefore, this study recommends a review of Regulation of the Minister of Home Affairs Number 7 of 2024 concerning Guidelines for the Management of Regional Government Property.